The Role of Social Capital in Community Based Tourism - Purwanti Dyah Pramanik; Rahmat Ingkadijaya; Mochamad Achmadi (Journal of Indonesian Tourism and Development Studies, 2019)
The role of social capital in Community-based tourism (CBT) to reach local communities’ welfare is being the concern of tourism activities. Previous research found that social capital approach could be used to achieve sustainability and prosperity. Mutually beneficial trust and collective action among the member of the community as aspects of social capital played an important role to take off CBT. The study aimed to analyze the role of trust and collective action as elements of social capital on the local community of CBT Kampung Tajur and to examine the link between trust and collective action. This study was conducted on a sample of Kampung Tajur community which was appointed as CBT because its willingness to take collective action. The result showed that trust was a robust predictor of attending a religious meeting, participating in managing homestay, and joining for community work. On the other hand, the absence of attending a formal meeting and community meeting conducted by the community head did not have a link to trust among the community member.  Our findings suggested that due to well implementation of social capital role in terms of  trust and collective action, the community’s members must be encouraged as the subject in tourism activity by enhancing knowledge, empowerment, and inspiration based on local wisdom.Keywords: Collective action, Community-based Tourism, social capital, trust.